Transformation of Assessment Practices: Evaluation of the Implementation of Differentiated Assessment in the Garment Preparation Phase at Vocational High Schools - Prasetyaningtyas, Wulansari; Nurmasitah, Sita; Widihastuti, Widihastuti; Ghufron, Anik (Universitas Negeri Semarang, 2025)
This study aims to evaluate the implementation of differentiated assessment in the garment preparation phase of the Fashion Design and Production subject in vocational high schools (SMK). Differentiated assessment is a strategic approach that aligns evaluation with students’ readiness, interests, and learning profiles, and is strongly promoted by the Merdeka Curriculum. Using a mixed-methods approach and the CIPP (Context, Input, Process, Product) evaluation model, this study involved 10 teachers, 160 students, 3 school principals, and 2 program heads from selected SMKs in Semarang. Data were collected through document analysis, classroom observations, questionnaires, interviews, and focus group discussions. The results show that differentiated assessment is only partially implemented. Most teachers adapt task difficulty but rarely differentiate based on students’ learning styles or interests. Major obstacles include limited professional development, lack of contextualized assessment tools, and time constraints. Despite these challenges, the study finds that students exhibit higher engagement and improved performance when provided with flexible and personalized assessment options. The findings emphasize the need for structured teacher training, development of project-based differentiated assessment tools, and school policies that support inclusive evaluation practices. This study contributes to both local and global discourse by highlighting the practical implications of differentiated assessment in vocational education and strengthening its relevance within the context of Indonesia’s education reform.